Climate change, agriculture and rural livelihoods in developing countries - Maharjan, Keshav Lall; Joshi, Niraj Prakash (Advances in Asian Human-Environmental Research, 2013)
This book is about climate change and its relation to agriculture and rural livelihoods. It starts by providing a basic understanding of climate change science followed by the relation of climate change to agriculture, the impact of which is discussed based on the particular impact of climate change on plant and animal physiology. The book further discusses the inclusion of the agriculture sector in various international climate change negotiations. It also reviews the cost and opportunities for agricultural projects through international climate change regimes, specifically the Clean Development Mechanism under the Kyoto Protocol. With this background and case studies of Nepal, the book finally proceeds to an explanation of the methodologies used to assess the impact of climate change on agriculture.